Artificial Intelligence In English Language Learning: Advantages And Challenges - Wahyudi Badri; Solehan; Muhammad Parli (Teaching English and Language Learning English Journal, 2024)
Artificial Intelligence (AI) has revolutionized English language learning by introducing tools and systems that offer personalized learning paths, instant feedback, and greater accessibility for learners worldwide. This study explores the advantages and challenges of integrating AI into English language education, drawing on recent research and expert insights. AI-powered platforms enhance learning experiences through adaptive techniques that address individual learner needs, increase engagement with gamified content, and provide inclusivity for diverse socio-economic and cultural backgrounds. Tools like chatbots and natural language processing (NLP) applications have demonstrated significant improvements in language acquisition and motivation. However, challenges persist, including algorithmic biases, data privacy concerns, the digital divide, and the potential for over-reliance on AI at the expense of human interaction. The findings emphasize the need for collaborative efforts between educators, technologists, and policymakers to balance the transformative potential of AI with its limitations. By leveraging AI as a complement to traditional teaching methods, this study highlights the importance of fairness, transparency, and inclusivity in fostering an equitable and effective learning environment. These insights pave the way for innovative approaches to English language education in an increasingly globalized world.